Social Movements in China and Hong Kong The Expansion of Protest Space - Guiheux, Gilles; Kuah-Pearce, Khun Eng (ICAS Publications Series, 2009)
The starting point of this book is the acknowledgement that on one side Chinese individuals, freer from the constraints of the State, have to rely on their own efforts for their well-being and, on the other side, in some circumstances, they gather together to defend their interests. The individualisation of society goes hand in hand with the collective movements that emerged as a result of individual wants. There are not only internal factors leading to the emergence of collective forms of action, but also external ones and that's why the editors have chosen to encompass Hong Kong in their study. The authors argue that protest actions and movement taking place in the Mainland and Hong Kong have enabled both societies to expand their protest spaces. At a theoretical level, these developments lead us to reconceputalise citizenship as practised rather than as given.